Aluminum Doped Germanene Nanoribbons: A First Principles Investigation. Issue 204 (2nd January 2020) - Sharma, Varun; Srivastava, Pankaj
Abstract: The purpose of current investigation is to analyze the impact of Al when introduced as an impurity from Al-substrate to germanene monolayers using first principles approach. Here, zigzag germanene nanoribbons (ZGeNR) with Al as dopant were studied at various sites viz. center (C-doped), edge (E-doped), nearedge (NE-doped). Formation energy calculations have been performed to show that Al-doping is preferred at the edge site, thus E-doped ZGeNR (EFE = −3.46 eV) emerges as most stable configuration. Further, based on band structure and DOS profile analysis we reveal that unlike semi-metallic pristine ZGeNR, Al-doped ZGeNR are metallic in nature, promoting their utilities as nanoscale interconnects.